2019
DOI: 10.1177/0363546519872501
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of the Open Latarjet Procedure for Recurrent Anterior Shoulder Instability in Patients Older Than 40 Years

Abstract: Background: Subgroup analyses of the Latarjet procedure have suggested that age over 40 years is a risk factor for dislocation arthropathy. Purpose: To analyze long-term results of the open Latarjet procedure for recurrent anterior shoulder dislocation in patients at least 40 years of age. Study Design: Case series; Level of evidence, 4. Methods: A total of 39 consecutive patients (40 shoulders) with a mean age of 48 years (range, 40-66 years) at surgery were evaluated at a mean follow-up of 11.0 years (range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…The Latarjet procedure is associated with loss of active ROM, loss of active ER 14 up to 19°, and minimal loss of active IR. 26 In the current study, we included patients without any previous or revision surgery, with clear recurrent anterior instability before the Latarjet procedure, and without any contralateral shoulder pathology or multidirectional instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Latarjet procedure is associated with loss of active ROM, loss of active ER 14 up to 19°, and minimal loss of active IR. 26 In the current study, we included patients without any previous or revision surgery, with clear recurrent anterior instability before the Latarjet procedure, and without any contralateral shoulder pathology or multidirectional instability.…”
Section: Discussionmentioning
confidence: 99%
“…The Latarjet procedure for recurrent anterior shoulder instability is very reliable, with reported long-term recurrence rates usually <10%. 1 , 9 , 12 , 14 , 18 The stabilizing mechanisms of this procedure rely on the bone-block effect (ie, increasing glenoid surface area) as well as the sling effect (ie, dynamic tensioning of the lower part of subscapularis in abduction). 36 A split in the subscapularis muscle is required to transfer the coracoid bone block through the muscle and fix it to the anteroinferior glenoid neck.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Latarjet procedure has seen a resurgence in popularity in recent years, because of its high success rates, with studies reporting excellent long-term shoulder stability and low recurrence rates. 3 , 10 , 11 , 12 Therefore, it has been advocated for in patients with high risk factors for recurrence after an arthroscopic Bankart repair, with several scoring systems available to stratify risk, primarily focusing on glenoid bone loss, Hill-Sachs lesions, and involvement in collision sports. 13 , 14 , 15 , 16 Because of Latarjet’s nonanatomical nature and invasive approach, there have been concerns over the associated risk of complications, 17 , 18 such as bone block nonunion or resorption, fracture of the coracoid, or injury of the musculocutaneous nerve, either during the approach or during retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Ernstbrunner et al showed that the open Latarjet reliably restored anterior shoulder stability, however patients had a significant amount of dislocation arthropathy with 37% of cases showing severe arthritis progression. 73 …”
Section: Open Latarjet Techniquementioning
confidence: 99%